(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
A case of Trypanosoma congolense savannah type infection in a 4-year old German shepherd dog weighing 26-kg was presented to the Small Animal Clinic, University of Nairobi, Kenya, with the history of anorexia and difficulty in breathing. The clinical manifestations were fever, pale mucous membrane, dyspnea and wasting. Blood examination revealed the existence of trypanosome parasites, and showed mild anemia. Internal Transcribed Spacer (ITS) based polymerase chain reaction confirmed the presence of Trypanosoma congolense savannah type. Along with supporting therapy, the case was successfully managed using diminazene aceturate injection (dosed at 3.5 mg/kg body weight) through intramuscular route. Complete recovery of the case was observed on day 6 of post-treatment. http://dx.doi.org/10.5455/javar.2014.a33